2004
DOI: 10.1097/01.ju.0000132857.39680.ce
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Tadalafil in United States and Puerto Rican Men With Erectile Dysfunction

Abstract: Tadalafil (20 mg) significantly improved erectile function and patients did not closely temporally link sexual intercourse attempts with taking tadalafil. Tadalafil was also well tolerated in both groups of men with mild to severe ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 8 publications
7
17
1
2
Order By: Relevance
“…Patients who received 20 mg tadalafil in this analysis had, on average, an IIEF-EF domain score of 23.0 at the end point, corresponding to mild ED as defined by Cappelleri et al [18]. The mean success rate for intercourse attempts (SEP3) with 20 mg tadalafil was 70.5%, which is comparable to results reported in Japan (69.4%) [25], the US and Puerto Rico (67.6%) [24], Canada (61.5%) [22], and Western Europe (73.9%) [23].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Patients who received 20 mg tadalafil in this analysis had, on average, an IIEF-EF domain score of 23.0 at the end point, corresponding to mild ED as defined by Cappelleri et al [18]. The mean success rate for intercourse attempts (SEP3) with 20 mg tadalafil was 70.5%, which is comparable to results reported in Japan (69.4%) [25], the US and Puerto Rico (67.6%) [24], Canada (61.5%) [22], and Western Europe (73.9%) [23].…”
Section: Discussionsupporting
confidence: 77%
“…This integrated analysis of 1 046 Asian men with ED showed that treatment with tadalafil at 10 mg or 20 mg improves The improvements in erectile function observed in this Asian population mirror those observed in earlier studies in Western populations [22][23][24]. Patients who received 20 mg tadalafil in this analysis had, on average, an IIEF-EF domain score of 23.0 at the end point, corresponding to mild ED as defined by Cappelleri et al [18].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The IIEF has been shown to be valid cross-culturally, 16 and its adaptation to Asian languages has not been associated with problems of comprehension. 13 All three measures have been widely used in clinical studies to assess the efficacy of ED therapy Mild (17)(18)(19)(20)(21)(22)(23)(24)(25) Moderate (11)(12)(13)(14)(15)(16) Severe (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) and are complementary to each other. Tadalafil at doses of 10-mg and 20-mg resulted in consistent and robust improvements in erectile function in South-East Asian men with ED based on all three measures.…”
Section: Discussionmentioning
confidence: 99%
“…131 In a trial of 207 US and Puerto Rican men, it was shown that the most successful intercourse attempts occurred between 4 and 36 h after taking tadalafil with 83% of men taking tadalafil reporting improved erections vs 20% placebo. 132 Another study confirmed the efficacy and adverse effect profile with tadalafil, and also showed that patients and their sexual partners were more satisfied than those given placebo. 133 Improved sexual satisfaction with tadalafil 10 and 20 mg has also been reported in men with mild, moderate and severe ED.…”
Section: Clinical Trials With Tadalafilmentioning
confidence: 76%